2007
DOI: 10.1080/02713680601160610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Macular Changes After Uncomplicated Phacoemulsification Surgery by Optical Coherence Tomography

Abstract: INTRODUÇÃO Edema macular (EM) permanece sendo a causa mais frequente de baixa visão após cirurgia de catarata (1,2). O EM desenvolve-se devido à quebra da barreira hematorretiniana causando acúmulo de líquido no espaço extracelular da retina e formação de cistos nas camadas plexiforme externa e nuclear interna (3,4). A incidência de EM à angiografia (3-70%) e de EM clinicamente relevante (0-22%) variam substancialmente na literatura, dependen-do da sua definição, técnica da cirurgia, método diagnóstico utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
116
2
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 16 publications
20
116
2
11
Order By: Relevance
“…In previous studies, subclinical macular thickening has been reported after uncomplicated cataract surgery. [9][10][11][12][13][14] Interestingly, in our study, at day 1 after surgery, mean retinal thickness of all macular subfields of the operated eyes decreased significantly in comparison to the fellow eyes. Retinal thickness on the first post-operative day showed significant increase in two studies 9,10 and mild statistically insignificant decrease in one study.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…In previous studies, subclinical macular thickening has been reported after uncomplicated cataract surgery. [9][10][11][12][13][14] Interestingly, in our study, at day 1 after surgery, mean retinal thickness of all macular subfields of the operated eyes decreased significantly in comparison to the fellow eyes. Retinal thickness on the first post-operative day showed significant increase in two studies 9,10 and mild statistically insignificant decrease in one study.…”
Section: Discussionsupporting
confidence: 42%
“…Retinal thickness on the first post-operative day showed significant increase in two studies 9,10 and mild statistically insignificant decrease in one study. 11 Therefore, our study is the first to show statistically significant decrease. It would seem reasonable to presume that retinal thickness does not vary or increase due to surgery-induced inflammation shortly after cataract extraction.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This compared with rates detected by SD-OCT in normal eyes after cataract surgery of between 4 and 11%. 14,15 Although CMO is a recognized late complication of choroideremia itself, 16 no patients in this cohort developed postoperative CMO. …”
Section: Discussionmentioning
confidence: 82%
“…Perente. [6] In the present study, there were 7 diabetics among which 4 showed increase in macular thickness post-operatively especially in inner nasal, inner inferior and central foveal areas. A study conducted by Soon II Kwon.…”
Section: Discussionmentioning
confidence: 95%